2006
DOI: 10.1038/sj.gene.6364351
|View full text |Cite
|
Sign up to set email alerts
|

Psoriasis: genetic associations and immune system changes

Abstract: Psoriasis is a common inflammatory skin disease characterized by infiltration of inflammatory cells into the epidermis and altered keratinocyte differentiation. Psoriasis is currently thought of as a T-cell mediated 'Type-1' autoimmune disease. Gene expression changes in psoriasis lesions have been well documented, and strongly support an important role for tumor necrosis factor and interferon gamma signal pathways in its pathogenesis. The strongest genetic determinant of psoriasis identified to date lies with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
147
0
18

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(166 citation statements)
references
References 98 publications
(101 reference statements)
1
147
0
18
Order By: Relevance
“…Although the authors did not explore the mechanism of inhibition, their results are very similar to ours. Furthermore, in a recent study we reported failure of exogenous RA to induce CRABPII in psoriatic skin lesions [25], where IFNγ is markedly increased due to the inflammatory process [35].…”
Section: Does Ifnγ Impair Retinoid Signalling Due To Reduced Rar-levels?mentioning
confidence: 93%
See 1 more Smart Citation
“…Although the authors did not explore the mechanism of inhibition, their results are very similar to ours. Furthermore, in a recent study we reported failure of exogenous RA to induce CRABPII in psoriatic skin lesions [25], where IFNγ is markedly increased due to the inflammatory process [35].…”
Section: Does Ifnγ Impair Retinoid Signalling Due To Reduced Rar-levels?mentioning
confidence: 93%
“…The proinflammatory agents, PMA and IFNγ, are also powerful inducers of keratinocyte differentiation in vitro, although their mechanisms of action are different [32][33][34]. PMA is an activator of the protein kinase C (PKC) -AP-1 signalling pathway and as such a potent inducer of skin tumours, whereas IFNγ elicits a gene response resulting in skin inflammation [35]. The aim of the study was, by using these stimuli and co-addition of various synthetic retinoids and inhibitors of AP-1 activity, to try and correlate the differentiation process to changes in the retinoid signalling pathways of human keratinocytes.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 The nuclear receptor LXR-a has a welldocumented role in cholesterol homeostasis and inflammation. 7 Recently, the LXR-a gene has caught the imagination of dermatologists, 8,9 keeping in view the fact that LXR-a has crucial role in keratinocyte proliferation and differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Strong evidence suggests a multilocus model of inheritance in association with environmental factors. 1 The etiology of the disease is still unclear. In several cases, however, low molecular weight chemicals (LMWC), such as drugs, were identified as etiologic agents, and variants of genes responsible for metabolizing LMWC are risk factors.…”
mentioning
confidence: 99%